THE PREBIOTIC INFLUENCE OF INULIN ON GROWTH RATE AND ANTIBIOTIC SENSITIVITY OF Lactobacillus casei - DEBOLINA BANERJEE; RANJANA CHOWDHURY; PINAKI BHATTACHARYA (Innovare Journal of Engineering and Technology, 2016)
Objective:Â This research study is focused on the prebiotic effect of inulin on the antibiotic sensitivity of probioticÂ Lactobacillus caseiÂ and on the determination of functionality of specific growth rate (Âµ) of the probiotic bacteria on the concentrations of lactose (CL= 10-30g/L) and inulin (CIÂ = 0.164-0.625g/L) along with the optimization of growth condition through Response Surface Methodology. Methods:Â The sensitivity ofÂ Lactobacillus caseiÂ towards norfloxacin was determined using well diffusion method. Using the initial values of Âµ (h-1) ofÂ Â Lactobacillus caseiÂ at different values of CL(g/L) and CIÂ (g/L), the functionality of Âµ on the concentrations of the carbon sources have been derived and optimum condition has been identified. Results:Â AlthoughÂ L.caseiÂ is sensitive to norfloxacin, resistance is developed in presence of inulin. Quadratic model equation Âµ =0.83+0.054 * CLÂ -0.035* CIÂ -0.049* CLÂ * CIÂ -0.29* CLÂ 2Â -0.33* CIÂ 2Â Â is valid and the optimum value of specific growth rate is 0.8285h-1Â at Â CL=20g/L and CIÂ =0.32g/L.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Conclusion:Â The interesting observation of development of antibiotic resistance ofÂ L.caseiÂ in presence of inulin suggests that the intake of probioticÂ L casei, may be done along with prebiotic inulin when a patient is treated with antibiotics like norfloxacin. Moreover the model equation correlating the functionality of growth rate of L.casei on lactose and inulin will be helpful in fortifying the probiotic milk products and drugs with prebiotics like inulin. Â Â